대답:
아래를 봐주세요,
설명:
같이 # z = x + iy #
# (iz-1) / (z-i) = (i (x + iy) -1) / (x + iy-i) #
= # (ix-y-1) / (x + i (y-1)) #
= (x-i (y-1)) / (x-i (y-1)
= # ((ix- (y + 1)) (x-i (y-1))) / (x ^ 2 + (y-1) ^ 2) #
= # (ix ^ 2 + x (y-1) -x (y + 1) + i (y ^ 2-1)) / (x ^ 2 +
= (x ^ 2 + (y-1) ^ 2) # (x (y-1) -
= # (- 2x + i (x ^ 2 + y ^ 2-1)) / (x ^ 2 + (y-1) ^ 2) #
같이 # (iz-1) / (z-i) # 진짜 야.
# (x ^ 2 + y ^ 2-1) = 0 # 과 # x ^ 2 + (y-1) ^ 2! = 0 #
지금으로 # x ^ 2 + (y-1) ^ 2 # 두 개의 제곱의 합입니다. # x = 0 # 과 # y = 1 # 즉
만약 # (x, y) # 아니다 #(0,1)#, # x ^ 2 + y ^ 2 = 1 #